APPLICATION OF FIQH PROPOSALS TO THE DETERMINATION OF THE LINEAGE OF CHILDREN BORN OUT OF WEDLOCK - Rahmadani, Gema (AT-TAFAHUM: Journal of Islamic Law, 2024)
Application of The application of usul fiqh to the determination of the nasab of children born from out-of-wedlock pregnant marriages is a complex issue and often becomes a matter of debate among the circles. is a complex issue and is often debated among scholars and society. scholars and society. This research aims to explore the relevant principles of usul fiqh and their implications in determining the child's children's nasab in the context of Islamic law. The methods used include a qualitative approach qualitative approach through in-depth interviews, literature study, case analysis, and participatory observation. participatory observation. The results show that there are different views among scholars regarding the recognition of children's nasab, with some arguing that nasab is only valid in legally recognized marriages. arguing that nasab is only valid in a legally recognized marriage. However, there are also contemporary views that support the protection of children's rights and the recognition of nasab based on evidence or However, there are also contemporary views that support the protection of children's rights and the recognition of nasab based on evidence or recognition from the father. Research This study recommends the need for a more adaptive reinterpretation of the law to accommodate the interests of children, as well as accommodate the interests of children, as well as community education efforts to reduce social stigma. social stigma. The findings are expected to contribute to development of Islamic law that is more humanist and responsive to current social needs. social needs of today.